Pollution ecology of estuarine invertebrates - Hart, C. W. | Fuller, Samuel L. H. (Academic Press / New York, 1979)
Contents: Tread worms nematodo; Bryzoa (ectoprocta), Bristle worms (annelida; polychaets; Ostrocods; Arthropoda; crustacea; Copepodos; Crab; Shrimps